Relevance of Social Work Practice in Child Sexual Abuse in Uselu Community, Edo State, Nigeria - Bello, Osamuyi Aghasomwan; Eweka, Helen Ehi. (NIU Journal of Social Sciences; Vol 11 No 1 (2025): NIU Journal of Social Sciences, Vol. 11 No. 1, March 2025DO - 10.58709/niujss.v11i1.2081, 2025)
Child sexual abuse (CSA) remains a critical social issue with profound psychological and social consequences. Addressing this challenge requires effective social work interventions tailored to community-specific needs. This study evaluates the relevance of social work practice in addressing CSA in Uselu Community, Edo State, Nigeria. The objectives were to explore the prevalence and underlying factors of CSA and assess the effectiveness of social work intervention practices. A cross-sectional survey design was employed, using a structured questionnaire to collect data from 384 respondents, with a 95.6% response rate. Findings revealed significant awareness of CSA, with 66.8% acknowledging its prevalence, though 33.2% remained unaware, highlighting gaps in awareness efforts. The home was identified as the most common site of abuse (49.0%), followed by schools (25.8%) and religious institutions (12.8%). Poverty (44.4%) and lack of parental supervision (35.9%) emerged as primary contributing factors. Social work interventions practices were rated as effective, with 48.5% of respondents considering counseling services very effective and 62% acknowledging effective collaboration with law enforcement. However, gaps exist in resource adequacy and outreach initiatives. The study recommends enhanced counseling services, stronger collaboration with law enforcement, increased resource allocation, and expanded community education programs to effectively combat CSA. Keywords: Child sexual abuse, social work practice, prevalence, intervention effectiveness, community awareness.